TRANFORMASI PERMUKIMAN PEDESAAN KE PERKOTAAN DI DAERAH PINGGIRAN KOTA SURAKARTA (STUDI KASUS KELURAHAN MOJOSONGO) - DANARTI Karsono (Jurnal Teknik Sipil dan Arsitektur, 2001)
Urbanization in Indonesia and generally still be called weak. The Indonesia population is, for a great part, still in the rural areas, nevertheless at this moment the city population has a very fas growth of (± 4%) much faster than the growth of the rural population (±1%). The settlement’s necessity especially for the middle class in cities can only be fulfilled in suburban areas, because  the prices of land on these areas is still relatively low to get a house along with its premeans. This research takes the case in Mojosongo village, in which city development is already visible in its suburban area, which changes the rural area with its ricefields into an urban area, which is full of buildings. The problem which needs to be studied for this case, is among other things, to solve the trend of the development of suburban areas. When a change or shift of land use takes place, the research method applied is the analyzis descriptive method, that of joint qualitative an quantitative nature, supplyed by a map analyzis, both about the physical things and its settlement. In its discussion, first of all, urbanization is observed, which is one of the factors, causing the development  of the Surakarta city. Further on, the dynamics of macro space change is also analyzed, both on its settlement aspect and on its physical one. Conclusions and suggestions of this research are among other things, the presentation of the process result of rural space transformation in a suburb, which will enrich the perception of all sides to the result of sub-urbanization in a suburb as a consequance of a city development.